Farming Families in Malaysia and the Philippines: Empirical Works and Classical Debates - Gregorio, Veronica L. (Animo Repository, 2019)
Family studies is a developing field in Southeast Asia. Scholars attempt to touch on family relations as they cover issues on national identity, state policies, gender division of labor, migration, agriculture, and modernization. It is important to give particular focus on the farming families in the region because, of all types of families, they are the ones who face and adapt to most changes in political, economic, cultural, and social terms. By reviewing literatures done in relation to farming families in Malaysia and the Philippines, this paper argues for the importance of (1) acknowledging the convergence in the definition and usage of the terms “family” and “kinship” in studying different forms of families, (2) exploring contemporary sociocultural perceptions on the family farm, and (3) ensuring that scholarly works go beyond focusing on development approaches and wife-husband dyad relations. Towards the conclusion, this work highlights the possibility of exploring Geertz and Ellen’s ecological approach in studying the role of the land in the strengthening or weakening of family relations. It also recommends Agarwal’s bargaining approach be extended to Southeast Asia and that siblingship and generational positionalities be considered.